New Insights into the Mechanism of Action of the Cyclopalladated Complex (CP2) in Leishmania: Calcium Dysregulation, Mitochondrial Dysfunction, and Cell Death - Velásquez, Angela Maria Arenas; Bartlett, Paula; Linares, Irwin Alexander Patino; Passalacqua, Thais G.; Teodoro, Daphne D. L.; Imamura, Kely B.; Virgilio, Stela; Tosi, Luiz R. O.; Leite, Aline de Lima; Buzalaf, Marilia A. R.; Velasques, Jecika M.; Netto, Adelino V. G.; et al. (American Society for Microbiology, 2022)
The current treatment of leishmaniasis is based on a few drugs that present several drawbacks, such as high toxicity, difficult administration route, and low efficacy. These disadvantages raise the necessity to develop novel antileishmanial compounds allied with a comprehensive understanding of their mechanisms of action. Here, we elucidate the probable mechanism of action of the antileishmanial binuclear cyclopalladated complex [Pd(dmba)(m-N3)]2 (CP2) in Leishmania amazonensis. CP2 causes oxidative stress in the parasite, resulting in disruption of mitochondrial Ca2+ homeostasis, cell cycle arrest at the S-phase, increasing the reactive oxygen species (ROS) production and overexpression of stress-related and cell detoxification proteins, and collapsing the Leishmania mitochondrial membrane potential, and promotes apoptotic-like features in promastigotes, leading to necrosis, or directs programmed cell death (PCD)-committed cells toward necrotic-like destruction. Moreover, CP2 reduces the parasite load in both liver and spleen in Leishmania infantum-infected hamsters when treated for 15 days with 1.5 mg/kg body weight/day CP2, expanding its potential application in addition to the already known effectiveness on cutaneous leishmaniasis for the treatment of visceral leishmaniasis, showing the broad spectrum of action of this cyclopalladated complex. The data presented here bring new insights into the CP2 molecular mechanisms of action, assisting the promotion of its rational modification to improve both safety and efficacy.
Other grants supported: Programa de Apoio ao Desenvolvimento Científico da Faculdade de Ciências Farmacêuticas da UNESP (PADC); and funding from the Thomas P. Infusino Endowment at Rutgers University. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior-Brasil (CAPES)-finance code 001 (I.A.P.L., T.G.P., K.B.I., and J.M.V.). M.A.R.B., A.V.G.N., and M.A.S.G. are recipients of a Research Productivity Scholarship from the National Council for Research and Development (CNPq).
Keywords: binuclear cyclopalladated complex; cutaneous leishmaniasis; necrotic death; calcium homeostasis; mitochondria; Leishmania; leishmanicidal activity